New therapeutic advances in the management of preeclampsia: A narrative review - Tabares-Beltrán, Nicoll Vanessa (2025)
Objective: To review emerging therapies targeting the pathophysiology of preeclampsia, including anti-inflammatory approaches, therapies targeting the complement system, anti-angiogenic factors and mesenchymal stem cells. Material and methods: A comprehensive search was performed in databases such as Medline and PubMed, without time restrictions, including research on innovative treatments. Results: Therapies such as statins, complement inhibitors, mesenchymal stem cells and apheresis have demonstrated potential to modulate inflammation, correct angiogenic imbalances and prolong gestation in cases of severe preeclampsia. Conclusion: These therapies offer promising approaches to improve maternal-fetal outcomes. Further multicenter research and interdisciplinary collaborations are essential to validate their efficacy and safety in clinical practice.